Engineered Bio‐inspired Multifunctional Peptide‐ and Protein‐based Therapeutic Biomolecules for Better Wound Care. Issue 24 (8th November 2021) - Gayen, Paramita; Jan, Somnath; Chowdhury, Nilkanta; Ghosh, Snehasish; Hembram, Monjuri; Bagchi, Angshuman; Sinha Roy, Rituparna
Abstract: Developing non‐immunogenic therapeutic biomolecules for facilitating blood clotting followed by wound healing via therapeutic angiogenesis, still remains a formidable challenge. Excessive blood loss of accident victims and battalions cause a huge number of deaths worldwide. Patients with inherited bleeding disorders face acute complications during injury and post‐surgery. Biologically‐inspired peptide‐based hemostat can act as a potential therapeutic for handling coagulopathy. Additionally, non‐healing wounds for patients having ischemic diseases can cause severe clinical complications. Advancement in stabilized growth‐factor‐based proangiogenic therapy may offer effective possibilities for the treatment of ischemic pathology. This review will discuss nature‐inspired biocompatible stabilized peptide‐ and protein‐based molecular medicines to serve unmet medical challenges for handling traumatic coagulopathy and impaired wound healing. Abstract : Engineering complete wound care, comprising blood clotting and healing of wound through therapeutic angiogenesis, continues to be a difficult task. This minireview comprehensively summarizes bio‐inspired stabilized peptide/protein based multiscale regenerative biomedicines as total wound care which can be potentially translated into clinics to serve the unmet medical challenges.